2018
DOI: 10.1002/jcb.27150
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of RNA interference–mediated E‐selectin gene silencing on cell adhesion molecule expression and cell‐cell adhesion in vascular endothelial cells in mice with immunologic contact urticaria

Abstract: Contact urticaria is recognized as the wheal and flare reaction at a site from direct contact with a chemical or protein agent. Ongoing studies have proposed that gene silencing may have a promising future in finding optimal treatment of a variety of disease; hence, the aim of the study was to investigate the effect of RNA interference-mediated E-selectin ( SELE) gene silencing on cell adhesion molecule expression and on cell-cell adhesion in vascular endothelial cells (VECs) in a mouse model of immunologic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It is reported that SELE is significantly upregulated in skin lesions in urticaria and may be involved in the pathogenesis of urticaria [32]. Meng et al [33] constructed a contact urticaria mouse model by inducing anti-dinitrophenol immunoglobulin E combined with 2,4-dinitrofluorobenzene. Next, the deletion of SELE by siRNA showed that E-selectin, intercellular cell adhesion molecule-1, CD62L, and eosinophil cationic protein expressions in the mouse skin significantly decreased compared with the initial levels and the adhesion of leukocytes receded, indicating that inhibiting SELE expression can reduce the adhesion of leukocytes and greatly weaken the inflammatory response in CSU, thus may act as a biomarker in CSU treatment [33].…”
Section: Cell Adhesion/chemotaxis Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that SELE is significantly upregulated in skin lesions in urticaria and may be involved in the pathogenesis of urticaria [32]. Meng et al [33] constructed a contact urticaria mouse model by inducing anti-dinitrophenol immunoglobulin E combined with 2,4-dinitrofluorobenzene. Next, the deletion of SELE by siRNA showed that E-selectin, intercellular cell adhesion molecule-1, CD62L, and eosinophil cationic protein expressions in the mouse skin significantly decreased compared with the initial levels and the adhesion of leukocytes receded, indicating that inhibiting SELE expression can reduce the adhesion of leukocytes and greatly weaken the inflammatory response in CSU, thus may act as a biomarker in CSU treatment [33].…”
Section: Cell Adhesion/chemotaxis Pathwaymentioning
confidence: 99%
“…Meng et al [33] constructed a contact urticaria mouse model by inducing anti-dinitrophenol immunoglobulin E combined with 2,4-dinitrofluorobenzene. Next, the deletion of SELE by siRNA showed that E-selectin, intercellular cell adhesion molecule-1, CD62L, and eosinophil cationic protein expressions in the mouse skin significantly decreased compared with the initial levels and the adhesion of leukocytes receded, indicating that inhibiting SELE expression can reduce the adhesion of leukocytes and greatly weaken the inflammatory response in CSU, thus may act as a biomarker in CSU treatment [33]. CCL17/miR-125a-5p CCL17 is a chemokine tracking Th2 cells and involved in a variety of Th2-mediated inflammatory diseases, including atopic dermatitis [34].…”
Section: Cell Adhesion/chemotaxis Pathwaymentioning
confidence: 99%
“…A previous study revealed that significantly decreased SELE serum levels may reflect the inhibitory activity on neutrophil rolling and extravasation towards inflamed skin [27]. SELE silencing has been shown to potentially inhibit the development of immunologic contact urticaria by inhibiting the cell adhesion ability of vascular endothelial cells [28]. In the present study, we detected that SELE silencing could prevent the production of TNF-α, HRF, IL-6, and histamine from mast cells and consequently ameliorate the progression of CIU.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibited secretion of IL-6 and TNF-α from mast cells may contribute to the treatment of allergic inflammation [29]. A previous study highlighted elevated levels of histamine as well as an increased positive expression rate of SELE as indicators of the successful establishment of mouse models of immunologic contact urticaria [28], suggesting a positive correlation between histamine and SELE. Besides, an increased endothelial surface expression of SELE has been reported to exert a synergistic effect on histamine and TNF-α [30].…”
Section: Discussionmentioning
confidence: 99%